A Cdk9–PP1 switch regulates the elongation–termination transition of RNA polymerase II - Parua, Pabitra K.; Booth, Gregory T.; Sansó, Miriam; Benjamin, Bradley; Tanny, Jason C.; Lis, John T.; Fisher, Robert P. (Nature (London), 2018)
The end of the RNA polymerase II (Pol II) transcription cycle is strictly regulated to prevent interference between neighbouring genes and to safeguard transcriptome integrity 1 . The accumulation of Pol II downstream of the cleavage and polyadenylation signal can facilitate the recruitment of factors involved in mRNA 3′-end formation and termination 2 , but how this sequence is initiated remains unclear. In a chemical–genetic screen, human protein phosphatase 1 (PP1) isoforms were identified as substrates of positive transcription elongation factor b (P-TEFb), also known as the cyclin-dependent kinase 9 (Cdk9)–cyclin T1 (CycT1) complex 3 . Here we show that Cdk9 and PP1 govern phosphorylation of the conserved elongation factor Spt5 in the fission yeast Schizosaccharomyces pombe . Cdk9 phosphorylates both Spt5 and a negative regulatory site on the PP1 isoform Dis2 4 . Sites targeted by Cdk9 in the Spt5 carboxy-terminal domain can be dephosphorylated by Dis2 in vitro, and dis2 mutations retard Spt5 dephosphorylation after inhibition of Cdk9 in vivo. Chromatin immunoprecipitation and sequencing analysis indicates that Spt5 is dephosphorylated as transcription complexes traverse the cleavage and polyadenylation signal, concomitant with the accumulation of Pol II phosphorylated at residue Ser2 of the carboxy-terminal domain consensus heptad repeat 5 . A conditionally lethal Dis2-inactivating mutation attenuates the drop in Spt5 phosphorylation on chromatin, promotes transcription beyond the normal termination zone (as detected by precision run-on transcription and sequencing 6 ) and is genetically suppressed by the ablation of Cdk9 target sites in Spt5. These results suggest that the transition of Pol II from elongation to termination coincides with a Dis2-dependent reversal of Cdk9 signalling—a switch that is analogous to a Cdk1–PP1 circuit that controls mitotic progression 4 . The kinase Cdk9 and the phosphatase Dis2 regulate the termination of transcription in fission yeast in part by controlling the phosphorylation state of the elongation factor Spt5.